Synthesis of CIGS powders: Transition from binary to quaternary crystalline structure - Lee, Eunjoo; Cho, Jin Woo; Kim, Jaehoon; Yun, Jaeho; Kim, Jong Hak; Min, Byoung Koun (ELSEVIER SCIENCE SA, 2010)
A chalcogenide quaternary crystal (CIGS) composed of Cu, In, Ga, and Se was synthesized by a solution reaction of Cu, In, and Ga nitrate and Se chloride in organic solvent, followed by an annealing process. In our synthetic method, the binary crystal of CuCl was found to be initially formed during the solution reaction at 130 degrees C for 3 h, but it turned into another binary crystal structure, beta-CuSe at the longer time reaction (>12 h). The binary crystalline structure was then turned into quaternary crystal due to the heat treatment at 450 degrees C in reduction conditions and in the absence of additional elemental sources of In and/or Ga. For potential solar cell applications, the powder was also applied to prepare CIGS film by a paste coating. The structural characteristics of the powder and film were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electronic diffraction (SAED), and scanning electron microscopy (SEM). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: SOLAR-CELLS; CU(IN,GA)SE-2 NANOPARTICLES; HIGH-EFFICIENCY; SELENIZATION; NONVACUUM; CUINSE2; ROUTE; INKS